Mula Wowowee hanggang Ultra: Telebisyon, Uri at Ideolohiya [From Wowowee to Ultra: Television, Class and Ideology] - Pangilinan, Choy (Philippine Humanities Review; Vol 14 No 2 (2012), 2015)
This paper is a critical intervention and interrogation of the noontime television show Wowowee which was televised from 5 February 2005 to 30 July 2010 in ABS-CBN 2. The show has then moved to ABC 5. Although its move to another TV network and the characteristics of its subsequent format deserve a separate paper, it can be said that the discursive language utilized by game shows rarewly deviate from the formulaic and profit-driven logic systemic to the media industry. This paper offers not only a specific mode of knowing and assessment of a particular television text (Wowowee) but also a theoretical grid and lens that might aid future scholars of television studies and popular culture who aim to dismantle the ramification of apolitical theorizations in the field of academic warfare and media criticism. I aim to problematize how televisual imageries, mediated significations, and regimes of discourses in television articulate a deodorized and depoliticized rendering of specific societal contradictions experienced by the broad masses through poverty, underdevelopment, and injustice. Coming from this theoretical position, I aim to show how the “culture industry,” such as the show Wowowee, legitimizes and authenticates existing power relations and modes of domination between contending classes in Philippine society. More specifically, how the show fabricates concrete ideological positions and mediated imaginings of intertwining discourses of class, poverty, and the politics of hope in order to incorporate and subsume the toiling masses to the hegemonic logic and character of the capitalist media industry and society. Pushing further my point, I attempt to demonstrate how the ideology of consumerism, commodification, and the ethos of liberalism serve as vital ideological imperatives that seamlessly This paper is a critical intervention and interrogation of the noontime television show Wowowee which was televised from 5 February 2005 to 30 July 2010 in ABS-CBN 2. The show has then moved to ABC 5. Although its move to another TV network and the characteristics of its subsequent format deserve a separate paper, it can be said that the discursive language utilized by game shows rarewly deviate from the formulaic and profit-driven logic systemic to the media industry. This paper offers not only a specific mode of knowing and assessment of a particular television text (Wowowee) but also a theoretical grid and lens that might aid future scholars of television studies and popular culture who aim to dismantle the ramification of apolitical theorizations in the field of academic warfare and media criticism. I aim to problematize how televisual imageries, mediated significations, and regimes of discourses in television articulate a deodorized and depoliticized rendering of specific societal contradictions experienced by the broad masses through poverty, underdevelopment, and injustice. Coming from this theoretical position, I aim to show how the “culture industry,” such as the show Wowowee, legitimizes and authenticates existing power relations and modes of domination between contending classes in Philippine society. More specifically, how the show fabricates concrete ideological positions and mediated imaginings of intertwining discourses of class, poverty, and the politics of hope in order to incorporate and subsume the toiling masses to the hegemonic logic and character of the capitalist media industry and society. Pushing further my point, I attempt to demonstrate how the ideology of consumerism, commodification, and the ethos of liberalism serve as vital ideological imperatives that seamlessly shape and re-shape the language of television in this era of global monopoly capital. Lastly, I aim to map out how the academic act of critical intervention can serve as counter-hegemonic position that will put premium to the political arena of academic criticism, much less, to the very act of reclaiming media and cultural production in order for it to justly serve the people. Thus, as I would assert, it is the tacit function of criticism and cultural production to radicalize and politicize the masses. As such, there is great importance in returning to ideological criticism and Marxism. Keywords: Television Studies, Popular Culture, Wowowee, Class, Globalization